Help-Seeking Behaviors Among Older Adults: A Scoping Review. (May 2022) - Teo, Kelly; Churchill, Ryan; Riadi, Indira; Kervin, Lucy; Wister, Andrew V.; Cosco, Theodore D.
Although older adults may experience health challenges requiring increased care, they often do not ask for help. This scoping review explores the factors associated with the help-seeking behaviors of older adults, and briefly discusses how minority ethnic populations can face additional challenges in help-seeking, due to factors such as language barriers and differing health beliefs. Guided by Arksey and O'Malley's scoping review framework and the Preferred Reporting Items for Systematic Reviews and Meta-AnalysesScoping Review guidelines, a systematic search of five databases was conducted. Using a qualitative meta-synthesis framework, emergent themes were identified. Data from 52 studies meeting inclusion criteria were organized into five themes: formal and informal supports, independence, symptom appraisal, accessibility and awareness, and language, alternative medicine and residency. Identifying how factors, including independence and symptom appraisal, relate to older adults' help-seeking behaviors may provide insights into how this population can be supported to seek help more effectively.